2020
DOI: 10.1101/2020.05.18.102038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutralizing antibody and soluble ACE2 inhibition of a replication-competent VSV-SARS-CoV-2 and a clinical isolate of SARS-CoV-2

Abstract: 25Antibody-based interventions against SARS-CoV-2 could limit morbidity, mortality, and 26 possibly disrupt epidemic transmission. An anticipated correlate of such countermeasures is the 27 level of neutralizing antibodies against the SARS-CoV-2 spike protein, yet there is no consensus 28 as to which assay should be used for such measurements. Using an infectious molecular clone 29 of vesicular stomatitis virus (VSV) that expresses eGFP as a marker of infection, we replaced the 30 glycoprotein gene (G) with th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 51 publications
3
130
0
Order By: Relevance
“…Thus SARS-CoV-2 vaccine development has bene ted from experience gained in the SARS-CoV vaccine studies. These studies demonstrated that neutralizing antibodies inhibit the interaction of spike protein with its receptor ACE2 and therefore prevent viral entry and replication (17,32,35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus SARS-CoV-2 vaccine development has bene ted from experience gained in the SARS-CoV vaccine studies. These studies demonstrated that neutralizing antibodies inhibit the interaction of spike protein with its receptor ACE2 and therefore prevent viral entry and replication (17,32,35).…”
Section: Discussionmentioning
confidence: 99%
“…A similar deletion of 19 amino acids in SARS-CoV-2 spike was also shown to enhance expression of SARS-CoV-2 in mammalian cells 24 . Moreover, several recent studies establishing pseudotyped SARS-CoV-2 BSL2 platforms reported the occurrence of one or two independent stop mutations, leading to 21 or 24 amino acids truncations in the cytoplasmic tail of SARS-CoV-2 spike 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this study was to examine the possibility of SARS-CoV-2 replication in the human intestine and potential fecal-oral transmission. A number of approaches and techniques, including scRNA-seq, human intestinal organoids, VSV-SARS-CoV-2-S-GFP chimeric virus (25), and wild-type SARS-CoV-2 virus, were used. The numbers of experimental and technical replicates in each group and the statistical analysis applied are described in the figure legends and in the "Statistical analysis" section.…”
Section: Methodsmentioning
confidence: 99%
“…Viruses VSV-SARS-CoV-2 GFP reporter chimeric virus was constructed by P.W.R. and S.P.J.W using the SARS-CoV-2 Wuhan-Hu-1 spike and the VSV Indiana strain (25). The virus was propagated in MA104 cells in T175 flasks.…”
Section: Plasmids Cells Reagents and Viruses Plasmidsmentioning
confidence: 99%